SERBUK BABAKAN AKASIA SEBAGAI PEREKAT PAPAN PARTIKEL - Suwardi Sumadiwangsa; Sadan Widarmana; Ratmaja Eka Putra; Rozak Memed (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
This work investigates the use of acacia (Acacia decurrens Willds.) bark powder mixed with paraformaldehyde as an adhesive for particleboard. The treatments included powder contents of 10, 12, and 14% of the oven dry weight basis. The paraformaldehyde employed has also 3 levels i.e. 20, 30, and 40%. Material used for this study was the jeungjing (Albizia falcataria (L.) Fosberg.) flakes. The boards were made in the Forest Products Research Centre laboratory to determine their physical and mechanical properties.The effect of paraformaldehyde content alone on the overall particleboards properties was not significant. On the other hand, the effect of acacia bark powder contents on the particle board properties were significant on water absorption, MOR and MOE after soaking. Those qualities were better with higher powder content.